Maternal Caffeine Consumption and Risk of Congenital Limb Deficiencies - Chen, Lei (Birth Defects Res A Clin Mol Teratol, 2012)
BACKGROUND: Animal studies have shown that high doses of caffeine might cause congenital limb deficiencies (LDs); however, no epidemiologic studies have explored this relation. METHODS: This case-control study assessed associations between maternal dietary caffeine and congenital LDs using data from the National Birth Defects Prevention Study (NBDPS), with 844 LD cases and 8069 controls from 1997 to 2007. Caffeine intakes from beverages (coffee, tea, and soda) and chocolate combined and by beverage type were examined. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were estimated for subtypes of isolated LDs (no additional major anomalies) and LDs with other major anomalies separately, comparing the odds of 10 to <100, 100 to <200, 200 to <300, and 300+ mg/day total caffeine intake to 0 to <10 mg/day. RESULTS: All total dietary caffeine intake categories of 10 mg/day and above were marginally associated with odds of all isolated LDs combined (aOR, 1.4–1.7), isolated longitudinal LDs (aOR, 1.2–1.6), and isolated transverse LDs (aOR, 1.3–1.8) compared to the lowest intake category. A dose-response pattern for total dietary caffeine intake was not observed. CONCLUSIONS: A weak increased risk of congenital LDs associated with maternal dietary caffeine consumption was observed in this study; however, risk did not vary by amount of caffeine consumed.